Prognostic biomarkers for cholangiocarcinoma (CCA): state of the art. (4th May 2021) - Lang, Sven A.; Bednarsch, Jan; Joechle, Katharina; Amygdalos, Iakovos; Czigany, Zoltan; Heij, Lara; Ulmer, Tom F.; Neumann, Ulf P.
ABSTRACT: Introduction :Although advances in understanding the molecular basis of cholangiocarcinoma (CCA) have been made, surgery is the only curative therapy option and the overall prognosis of patients suffering from the disease remains poor. Therefore, estimation of prognosis based on known and novel biomarkers is essential for therapy guidance of CCA in both, curative and palliative settings. Areas covered :An extensive literature search on biomarkers for CCA with special emphasis on prognosis was performed. Based on this, prognostic biomarkers from serum, tumor tissue and other compartments that are currently in use or under evaluation for CCA were summarized in this review. Furthermore, an overview of new biomarkers was provided including those determined from extracellular vesicles (EVs), metabolites and nucleic acids. Finally, prognostic markers associated with potential new therapy options for the treatment of CCA were summed up. Expert opinion :So far, an optimal prognostic biomarker for CCA has not been described. However, based on the increasing knowledge about the molecular basis of CCA but also due to novel, innovative technologies, a plethora of novel prognostic biomarkers is currently under evaluation and will be available for CCA in future.